Avaliação de pastas álcali-ativadas produzidas com resíduos industriais e ativador alternativo - Vanzetto, Suelen Cristina (2023)
Alkali activated pastes are materials being researched as an alternative to Portland cement in some construction applications. Its amorphous three-dimensional structure comes from the reaction between precursor materials, composed of aluminosilicates, and alkaline solution. In this context, the objective of this study is to evaluate the use of industrial waste, ETA sludge, glass cutting powder and sugar cane bagasse ash, as precursors for the production of alkaliactivated pastes with conventional Sodium Silicate and Sodium Silicate. Sodium Alternative from rice husk ash. The proposed experimental method is divided into different phases: (1) selection and characterization of raw materials, (2) determination of the production conditions of an alternative alkaline activator based on the dissolution of rice husk ash (3) evaluation of alkali pastes activated by sodium hydroxide and commercial sodium silicate (4) evaluation of alkali pastes activated by sodium hydroxide and alternative sodium silicate from rice husk ash. From the analysis of results, it was observed that the waste contains silica in its composition, which is directly linked to the reactivity and polymerization process. For the production of alternative silicate, the results demonstrated the efficiency of the silicate produced, confirming the potential for using rice husk ash in alkali activated materials. The use of commercial sodium hydroxide and sodium silicate showed satisfactory results for the production of alkali activated pastes. When using alternative silicate with rice husk ash, the alkali activated pastes showed similar behavior to commercial silicate, which indicates the feasibility of using the alternative silicate as a complementary source of silica. In general, the results of this study show that the use of industrial waste, with a commercial or alternative source of silica in the production of alkali activated pastes brings positive perspectives.